1994
DOI: 10.1152/ajpregu.1994.267.4.r929
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulation in mice during withdrawal from ethanol dependence

Abstract: Temperature regulation during withdrawal from ethanol dependence was studied in mice. Dependence was induced utilizing ethanol vapor inhalation combined with injections of pyrazole, an alcohol dehydrogenase inhibitor. One control group received vehicle (0.9% NaCl); another received pyrazole (68.1 mg/kg) in vehicle. During withdrawal, mice were placed in a thermal gradient, with core temperature (Tc) and preferred temperature (Tpref) continuously recorded for 26 h. During the period of maximal withdrawal severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Results from Experiments 3 and 4 revealed that effects of chronic EtOH withdrawal on nest building were more pronounced during early stages of withdrawal (i.e., the first 24 h) when EtOH withdrawal-induced reductions in thermal set point have been observed. HS/Ibg mice were generally more motivated to seek cooler environments when tested in thermal gradients 1–26 h after chronic EtOH vapor inhalation, and this change in preference occurred in the absence of reduced core body temperature [13]. EtOH-withdrawing mice also displayed greater variability in preferred temperatures than either mice that breathed air and had been given daily injections of pyrazole in saline or injections of saline alone during the initial 10–11 hours after exiting the vapor chambers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from Experiments 3 and 4 revealed that effects of chronic EtOH withdrawal on nest building were more pronounced during early stages of withdrawal (i.e., the first 24 h) when EtOH withdrawal-induced reductions in thermal set point have been observed. HS/Ibg mice were generally more motivated to seek cooler environments when tested in thermal gradients 1–26 h after chronic EtOH vapor inhalation, and this change in preference occurred in the absence of reduced core body temperature [13]. EtOH-withdrawing mice also displayed greater variability in preferred temperatures than either mice that breathed air and had been given daily injections of pyrazole in saline or injections of saline alone during the initial 10–11 hours after exiting the vapor chambers.…”
Section: Discussionmentioning
confidence: 99%
“…These states are disrupted in mice over various time periods during withdrawal from chronic EtOH. During the initial 24 hours of withdrawal from three days of chronic EtOH vapor inhalation, dysregulated body temperature [13] and motor abnormalities (e.g., increased tremor) [14] were observed in mice from a genetically heterogeneous stock and in mice selectively bred for severe EtOH withdrawal HICs, respectively. Longer-lasting motor impairments on the balance beam and accelerating rotarod were dose-dependently induced by chronic EtOH vapor inhalation and observed up to 3 days after withdrawal in mice from a genetically segregating background [15].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, using WD Battery 1, we sought to replicate in HS/Npt mice multiple withdrawal-sensitive behaviors shown previously at approximately these hours of WD to reflect treatment effects (Kosobud & Crabbe, 1986; Crabbe et al, 2012; Philibin et al, 2008). We also included a test of anxiety-like behavior (Gorin et al, 2005) and assessed body temperatures (Crawshaw et al, 1994). Based on the results of WD Battery 1 (see Results, Anxiety-Like Behavior), we designed WD Battery 2 to test anxiety-like behavior without previously testing other withdrawal signs, followed by body temperature to verify the previous findings, and added a sucrose preference test to assess possible anhedonia (Muscat and Willner, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…These include tachycardia (increased heart rate), increased blood pressure, diaphoresis (heavy sweating), body temperature dysregulation, and gastrointestinal disturbances (nausea, vomiting). Animal models demonstrate many of these classic sympathomimetic withdrawal symptoms, including altered cardiovascular function, central and behavioral thermal dysregulation, diarrhea, and reduced food and water intake (Crawshaw et al 1994; Friedman 1980; Rasmussen et al 2006). However, given the complex and dynamic nature of variables that influence autonomic function, the reliability and practical utility of these measures is questionable (Bar et al 2006).…”
Section: Modeling Human Withdrawal Phenotypes In Animalsmentioning
confidence: 99%